Comparative Investigation of Synesthesia in “Sight al-Zand” by AbulʿAla Al-MaʿarriAnd the Poetical Works of Shoorideh-E-Shirazi - Javad Gholamalizadeh; Abdolbaset Arab Yosefabadi; Reza Asghari (مطالعات زبانی و بلاغی)
Rhetorical devices make literary works attractive and endow words with pleasant rhythm. Synesthesia, one of these devices, is applied to the combination of two or more senses in a way that increases words effect through creating spiritual rhythm. The concept was firstly introduced by Charles Baudelaire (1821-1876) in the nineteenth century. He divided synesthesia into 9 combinations and suggested specific principles per combination. Analyzing diverse types of Baudelaire synesthesia in the works of two Arabic and Persian blind poets, Abul Ala Al-Maarri (937-1057) and Shoorideh-Shirazi (1857-1927), using a descriptive-analytical method, the present study aims to demonstrate the beauty in blind poets’ poems which results from deep imagination. The results indicate that both poets seek to highlight images related to sight, especially sight-touch sense, in the combination of senses so that they can hide their disability from readers’ views.